Molecular stratification of medulloblastoma: comparison of histological and genetic methods to detect Wnt activated tumours. (February 2015) - Goschzik, Tobias; zur Mühlen, Anja; Kristiansen, Glen; Haberler, Christine; Stefanits, Harald; Friedrich, Carsten; von Hoff, Katja; Rutkowski, Stefan; Pfister, Stefan M.; Pietsch, Torsten
Abstract : Aims: Wnt activation in medulloblastomas is associated with good outcome. Upfront testing and risk‐adapted stratification of patients will be done in future clinical studies. In a cohort of 186 paediatric medulloblastomas our aim was to identify the optimal methods in standard clinical practice to detect this subgroup. Methods: Nuclear accumulation of β‐catenin was analysed by immunohistochemistry (IHC). DNA of FFPE tissue was amplified by PCR for single‐strand conformation polymorphism analysis and direct sequencing of CTNNB1 exon 3. Copy number of chromosome 6 was analysed by multiplex ligation‐dependent probe amplification and molecular inversion profiling. Results: Different automated immunostaining systems showed similar results. Twenty‐one of 186 samples had nuclear accumulation in ≥5% of cells, 17 samples showed <5% β‐catenin positive nuclei. None of these 17 cases had CTNNB1 mutations, but 18 of 21 cases with ≥5% accumulation did, identifying these 18 cases as Wnt‐subgroup medulloblastomas. Fifteen of 18 mutated cases showed monosomy 6, 3 had balanced chromosome 6. On the contrary, none of the CTNNB1 wild‐type tumours had monosomy 6. Conclusions: Standard neuropathological evaluation of medulloblastoma samples should include IHC of β‐catenin because tumours with high nuclear accumulation of β‐catenin most probably belong to the Wnt subgroup of medulloblastomas. Still, IHC alone may be insufficient to detect all Wnt cases. Similarly, chromosome 6 aberrations were not present in all CTNNB1 ‐mutated cases. Therefore, we conclude that sequencing analysis of CTNNB1 exon 3 in combination with β‐catenin IHC (possibly as pre‐screening method) is a feasible and cost‐efficient way for the determination of Wnt medulloblastomas.